Religious Differences in Educational Achievement - Syahrul Syahrul; Ratna Abdullah; Yayuk Julyyanti; Nur Wahida Yusuf (Institut Agama Islam Negeri Imam Bonjol Padang, 2025)
The purpose of this study was to determine differences in student learning outcomes of different religions at SMA Muhammadiyah Kalabahi, East Nusa Tenggara. This type of research is descriptive qualitative, namely a study of differences in student achievement and student learning outcomes. The research subjects consisted of teachers and students at SMA Muhammadiyah Kalabahi. Data collection techniques include observation, interviews, and documentation. The process of data analysis through data reduction, data presentation, and conclusion. The results of the study showed that there were differences in the learning achievements of students who were Muslim, Catholic and Protestant at SMA Muhammadiyah Kalabahi. Most Muslim students get good learning outcomes in science, while Catholic and Protestant students have good achievements in the arts.